2020
DOI: 10.24093/awej/vol11no1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of SPAWN Strategy in Developing Persuasive Writing Skills and Productive Habits of Mind

Abstract: This research investigated the effect of SPAWN strategy in developing persuasive writing skills and productive habits of mind in the English language among second secondary grade students. The study adopted the quasi-experimental design, which involves two groups: experimental and control. For data collection, the researcher designed the following instruments and materials: the teacher's guide to teach persuasive writing and develop productive habits of mind by using SPAWN strategy, persuasive writing skills t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…It has found that there are strong indications of high levels of reasoning and critical thinking in group discussion activities [18]. As well, adopting a quasi-experimental design, Alkthery and AI-Qiawi [19] investigated the effect of instructional strategy to enhance secondary grade students' pro-ductive habits of mind and English language persuasive writing and revealed a strong positive correlation between persuasive writing skills (Opinion or position, Reason and Support) and the productive habits of mind (Thinking flexibly, Questioning and Problem posing). Based on the above, it can be concluded that, understanding the habits of mind provides us with insights as to the nature of one individual's cognitive mechanism for the process of information gathering and conclusion drawing which can be regarded as a truly learning status.…”
Section: Habits Of Mindmentioning
confidence: 99%
“…It has found that there are strong indications of high levels of reasoning and critical thinking in group discussion activities [18]. As well, adopting a quasi-experimental design, Alkthery and AI-Qiawi [19] investigated the effect of instructional strategy to enhance secondary grade students' pro-ductive habits of mind and English language persuasive writing and revealed a strong positive correlation between persuasive writing skills (Opinion or position, Reason and Support) and the productive habits of mind (Thinking flexibly, Questioning and Problem posing). Based on the above, it can be concluded that, understanding the habits of mind provides us with insights as to the nature of one individual's cognitive mechanism for the process of information gathering and conclusion drawing which can be regarded as a truly learning status.…”
Section: Habits Of Mindmentioning
confidence: 99%
“…study(Musaed Alkthery and Abdullah Al-Qiawi, 2020) tries to determine the role of public transaction control in optimizing government spending. This is accomplished by debating how to provide oversight of public transactions.…”
mentioning
confidence: 99%